Plankton Community, Carbon-Nitrogen Ratios and Food Preference in Blind Feeding Phase of Litopenaeus vannamei - Maria Eva Kristiana; Suwarno Hadisusanto; Rustadi Rustadi (Universitas Gadjah Mada, 2023)
Litopenaeus vannamei is one of the largest commodities having a major impact on the global economy. Shrimp larvae have drastic changes in morphology and physiology which require extra maintenance. Feed management in early rearing using a blind feeding system which plankton as the main food. The relation between plankton and C/N needs to be investigated to optimize the growth of natural feed. The aims of the study were to analyze plankton community structure; the relationship between plankton to C/N and the environmental parameters; and determine the shrimp preferences of plankton. Data were collected at 3 points in 3 different ponds (PA, PB, PC) on day 8 and day 15 using a stratified sampling method with criteria (intensive system and blind feeding phase). Plankton density and C/N relationship were analyzed using Linear Regression, plankton and environmental parameters using Canonical Correspondence Analysis (CCA). Shrimp food preferences were analyzed descriptively in percentage. The results showed that diatoms and dinoflagellates dominated phytoplankton, and rotifers dominate zooplankton. C/N showed a positive correlation to protozoa, but a negative correlation to pennate diatoms and copepods. The most influential environmental factors for both phytoplankton and zooplankton density were temperature, C-organic, salinity, pH, alkalinity, and dissolved oxygen.